The results of Bogdanov and Bitchuk rods application for deformity correction of the low extremities in patients with osteogenesis imperfect - Khmyzov, Sergey; Pashenko, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Treatment of low extremities deformities in children with osteogenesis imperfect is still actually under 40 years. There are a lot of surgical methods, but number of complications is still high (from 30 to 50–60 %). Purpose: to make retrospective study of surgical results after deformities correction in children with osteogenesis imperfect with Bogdanov and Bitchuk rods. Methods: we studied data of 4 children (age 7–16 years old) with osteogenesis imperfect after 10 corrective surgeries with intramedullary fixators. Bitchuk rods were used in 2 femur segments and 2 tibia segments, Bogdanov rods-in 3 femur and 3 tibia segments. Low extremities deformities were 25°–122°, that limited loading and kinematic patient’s activity. Varus deformity was observed in 5 segments, valgus — 5, antecurvation — 10 segments. Results: the primary correction of deformity was achieved in all cases. In postoperative period fractures of the 4 rods were found (3 Bogdanov and 1 Bitchuk). Among them in 3 patients fracture fragments were consolidated with previous deformity, in 1 patient — femur fixator was changed. In 4 tibia segments fractures were consolidated with correction but with the fracture of blocked screws. Reoperation was needed in 1 case after usage of Bitchuk rod. Conclusions: Bitchuk intramedullary rods are better compare with Bogdanov rods for surgical correction of deformities in children with osteogenesis imperfect due to device design and the presence of blocked screws. It helps to achieve proper stability and to avoid deformity appearance. But the number of complications is high after the application of the both rods. There is need to perform further design of devices.